Effect of Existing Façade’s Construction and Orientation on the Performance of Low-E-Based Retrofit Double Glazing in Tropical Climate - Sivanand Somasundaram; Sundar Raj Thangavelu; Alex Chong (Energies, 2020)
This paper investigates the effect of an existing façade’s construction (viz. clear/grey/solar film, with and without external shade) and orientation on the performance of low-e (hard coat)-based retrofit double glazing in a tropical climate. The performance of double-glazed façades is characterized by the ability to reduce solar heat gain and the consequent reduction in power consumption of air-conditioning systems. This study involves a real-life test-bedding of a low-e (hard coat)-based retrofit double-glazing façade for a few specific cases—clear glass southeast façade without shade, clear glass southwest façade with external shade, and northwest façade with solar film and external shade. Subsequently, energy modelling simulations were done to analyze other scenarios involving various combinations of façade orientation (north, south, west, and east) and façade material (clear glass, tinted grey glass, clear glass with solar film) with and without external sunshades. The east/west-facing façades had a higher impact on the retrofit solution, and more so when the existing façade was of tinted glass or with solar film. For the case analyzed, with a window-to-wall ratio of 8% (based on overall building envelope), a grey tinted east-facing façade could benefit from annual average HVAC energy savings of up to 5.9%.